2013
DOI: 10.1179/1351000212y.0000000031
|View full text |Cite
|
Sign up to set email alerts
|

GSTM1-null and GSTA1-low activity genotypes are associated with enhanced oxidative damage in bladder cancer

Abstract: Our results suggest that absent GSTM1 or reduced GSTA1 antioxidant activity may increase the accumulation of oxidative DNA damage, thereby contributing to the malignant potential of TCC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 27 publications
2
6
0
Order By: Relevance
“…In the study of oxidative DNA modifications among malignant diseases, 8-OHdG seems to be the most appropriate biomarker. Indeed, bladder cancer patients, carriers of GSTM1-null and GSTA1variant genotypes, exhibited higher urinary 8-OHdG levels (Savic-Radojevic et al 2013). In this line, our results on the higher levels of 8-OHdG, a biomarker of free radicalinduced DNA-oxidative damage, among ccRCC patients with GSTO2*G/G variant genotype (rs2297235) seem plau-sible.…”
Section: Controls N (%) Patients N (%) or (95% Ci) A Psupporting
confidence: 74%
“…In the study of oxidative DNA modifications among malignant diseases, 8-OHdG seems to be the most appropriate biomarker. Indeed, bladder cancer patients, carriers of GSTM1-null and GSTA1variant genotypes, exhibited higher urinary 8-OHdG levels (Savic-Radojevic et al 2013). In this line, our results on the higher levels of 8-OHdG, a biomarker of free radicalinduced DNA-oxidative damage, among ccRCC patients with GSTO2*G/G variant genotype (rs2297235) seem plau-sible.…”
Section: Controls N (%) Patients N (%) or (95% Ci) A Psupporting
confidence: 74%
“…8-OHdG levels have also been evaluated in patients with different types of cancer. [23][24][25][26][27][28][29][30][31][32][33][34][35][36][37] No differences in urinary 8-OHdG values are generally found between patients with lung cancer and control groups. [26][27][28] However, Çobanoğlu et al 29 reported high 8-OHdG values in patients with cancer, and Yamamoto et al 23 reported significantly higher urinary 8-OHdG levels in patients with gynecological cancers compared to those in controls.…”
Section: Discussionmentioning
confidence: 99%
“…Eight isoforms of cytosolic-soluble GSTs have been recognized in humans, including α, κ, μ, π, σ, θ, ζ, and ω 3,4 . Glutathione S-transferase α1 (GSTA1, Gene ID: 2938) has shown both stimulatory [5][6][7][8] and inhibitory effects [9][10][11][12] on tumorigenesis. The association between genetic polymorphism of GSTA1 and susceptibility to cancer has been discussed in previous studies [13][14][15] , but…”
Section: Introductionmentioning
confidence: 99%